An analysis of the droplet support fiber effect on the evaporation process. (January 2019) - Chauveau, Christian; Birouk, Madjid; Halter, Fabien; Gökalp, Iskender
Highlights: Droplet support fiber effect on the evaporation in a hot atmospheric is studied. n -Heptane is selected because it is the most common fuel used in the literature. The cross-microfiber technique does not interfere with the evaporation process. The classical fiber technique enhances the droplet evaporation process. A correlation is proposed to quantify the effect of the droplet support fiber. Abstract: This paper presents an analysis of the effect of the droplet support fiber on the droplet evaporation process. This effect is evaluated for a droplet evaporating in a hot environment at atmospheric pressure using the experimental results of the present study and those in the literature. Selected published results are acquired using similar test conditions and experimental setups as the present data. The only main difference between these studies is the droplet support fiber diameter which varies between 14 µm and 225 µm. The ambient temperature explored in these studies ranges from room temperature up to 973 K. n -Heptane is selected because it is the most common fuel used in these studies. The main findings are that the cross-fiber technique, which uses 14 µm fiber diameters, induces no noticeable heat transfer into the droplet and consequently does not interfere with the evaporation process. In contrast, the classical fiber technique, which uses relatively larger fibers, greatly enhances the droplet evaporation rate as a consequence of increased conduction heat transfer through the fiber. A correlation is proposed to quantify the level of this increase as a function of ambient temperature and the fiber cross-sectional area, d f 2 .